THEORETICAL AND METHODOLOGICAL ASPECTS OF THE ANALYSIS OF IMPERFECT COMPETITION IN THE CONTEXT OF DIGITALIZATION (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the theoretical and methodological aspects of the analysis of the market of imperfect competition in the context of digitalization. Special attention is paid to the transformation of classical forms of competition under the influence of digital technologies, including platform models, algorithmic pricing and the role of big data. the need to update methodological analysis tools that take into account network effects, information asymmetry and digital infrastructure. Conclusions are made about the need to adapt competition policy to the challenges of the digital economy.